The Power of Social Movements: Activism in the Age of Connectivity - Laksana, Muhibudin Wijaya; Abduh, Muhammad (UIN Sunan Gunung Djati Bandung, 2023)
In an age where information flows rapidly across global networks, social movements have harnessed the power of digital connectivity for advocating change, justice, and equality. This abstract, employing qualitative research methods such as content analysis and participant observations, explores the intricate dynamics of contemporary social movements. Additionally, it synthesizes relevant literature, offering historical context and theoretical foundations that underpin modern activism. Through case studies and current trend analysis, this research sheds light on how connectivity has reshaped the activism landscape, presenting valuable insights into its implications for the future of social change efforts.